Choice theoretical foundations of union utility functions involving discontinuities - Δρακόπουλος Σταύρος Α. (SPOUDAI Journal of Economics and Business, 2004)
Trade Union utility functions with discontinuities have started to gain popularity in the last few years. The main reason for this is the search for more embracing union utility functions. The choice of the appropriate union utility function has important implications for analysing the problem of unemployment and wages in unionized labour markets. This paper attempts to provide the choice theoretical foundations of such functions thereby widening their relevance and facilitating their application to other areas. The foundations can also be used as a basis for modeling sequential multi-objective union utility functions. JEL Classification: J5